2021
DOI: 10.1038/s41598-021-91197-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation of gases competitive adsorption in lignite and analysis of original CO desorption

Abstract: To study the adsorption characteristics of CO, CO2, N2, O2, and their binary-components in lignite coal, reveal the influence of CO2 or N2 injection and air leakage on the desorption of CO in goafs, a lignite model (C206H206N2O44) was established, and the supercell structure was optimized under temperatures of 288.15–318.15 K for molecular simulation. Based on molecular dynamics, the Grand Canonical Monte Carlo method was used to simulate the adsorption characteristics and the Langmuir equation was used to fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…When the adsorption capacity of O 2 is higher than that of CO, air leakage should be controlled to prevent CO in coal seams containing primary CO from desorbing to improve the accuracy of predicting spontaneous coal combustion when CO is used as the index gas. 40 For no. 2 coal, compared with the CO 2 competitive adsorption capacity, the stronger adsorption capacity is shown by CO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the adsorption capacity of O 2 is higher than that of CO, air leakage should be controlled to prevent CO in coal seams containing primary CO from desorbing to improve the accuracy of predicting spontaneous coal combustion when CO is used as the index gas. 40 For no. 2 coal, compared with the CO 2 competitive adsorption capacity, the stronger adsorption capacity is shown by CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…38,39 Therefore, it is necessary to study the adsorption of CO in coal. Although Zhang et al 40 analyzed the competition between CO and other small molecules in lignite by molecular simulation, there is a lack of comparison of adsorption selectivity between CO and other small molecules. Therefore, we aimed to clarify the competitive characteristics and adsorption capacity between O 2 , CO 2 , and CO of bituminous coal, aiming at the occurrence and diffusion behavior of CO in coal seams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter settings of geometry optimization, energy optimization, and annealing optimization are shown in Table 1. 28,29 2.2. AMS Molecular Dynamics Simulation.…”
Section: Modeling and Computational Detailsmentioning
confidence: 99%
“…The allelic adsorption heat of CO 2 is nearly twice that of O 2 or N 2 , it occupies a stronger adsorption site without being affected by O 2 or N 2 , and the interaction energy between CO 2 and coal is greater than that of O 2 or N 2 . Zhang et al 20 found that the adsorption amount of a single component in coal is in the order of CO 2 > CO > O 2 > N 2 through simulation research. Bahamon, 21 Hauchhum et al 22 used MD to simulate the adsorption behavior of gases on activated carbon.…”
Section: Introductionmentioning
confidence: 99%